Beyond the familial: The development of emotional communication with mothers, fathers, and strangers. (11th April 2022) - Salvadori, Eliala A.; Colonnesi, Cristina; Elsammak, Linnea; Oort, Frans J.; Messinger, Daniel S.
Abstract: Interaction with unfamiliar partners is a component of social life from infancy onward. Yet little is known about preverbal communication with strangers. This study compared the development of infant communication with strangers to communication with mothers and fathers and examined the contribution of temperament to partner‐specific communication patterns. A sample of 58 infants was observed at four and eight months during separate home‐based face‐to‐face interactions with three partners (mother, father, and stranger). Infant visual, facial, and vocal communication behaviors were coded microanalytically. Each parent reported on infant temperament at both ages. Multilevel regression analyses indicated that infants gazed longer at strangers than at fathers, exhibited less smiling to strangers than to mothers, and produced fewer vocalizations with strangers than with either parent. Both age and temperament moderated these differences. Vocal communication with fathers became more frequent at eight months; smiling to mothers was accentuated among infants with higher levels of temperamental surgency. Importantly, levels of communication behaviors with strangers were concurrently and longitudinally associated with those with mothers and fathers. Overall, findings suggest that infant emotional communication patterns are modulated by individual temperamental differences and are reproduced in and over time, though at different levels, when interacting with novel partners.